The Effect of Choking under Pressure on the Predictive Performance of Elite and Novice Fencers - jafar Belali voshmehsara; Saeed Arsham; Shahab Parvinpour; Fazlollah Bagherzadeh (University of Tehran, 2021)
One of the key factors for success in sport competitions is the ability to predict the movements of an opponent before performing them. The aim of the present study was to determine the effect of choking under pressure on predictive performance and to compare it between elite and novice fencers. In this quasi-experimental study, the subjects included 15 elite athletes of the youth fencing national team (16-20 years old) and 15 students from University of Tehran (18-22 years old) as novice athletes who were assigned to two groups by convenience sampling method. Prior to the test, 15 clips out of 100 video clips of different attacks on different parts of the fencers' body were performed and recorded by two professional members of the Iran National Fencing Team. After each video clip was stopped (before the sword hit the opponent's body), an answer sheet appeared on the screen and the subjects had to predict the location where the sword hit the opponent. The present study was conducted under high and normal pressure conditions. The high pressure condition was applied by the presence of a national team coach as the evaluator and in the non-pressure condition, the efforts were made without the presence of the evaluator. The results of mixed factor analysis of variance showed that the main effect of condition and group was significant but the interactive effect of condition and group was not significant. Bonferroni post hoc test results also showed that those players who were in normal condition had better predictive performance than those who were under the pressure condition; also, elite players had better predictive performance than novices in both conditions (P<0.05). But generally, choking under pressure decreases predictive performance in both elite and novice fencers.